Fifteen-minute consultation: Emergency management of tracheostomy problems in children. Issue 4 (11th January 2019) - Ross, Elizabeth; Stephenson, Kate
Abstract : It is vital for healthcare professionals to have a basic understanding of tracheostomy tubes, including their routine and emergency care. Children with tracheostomies can be encountered in all areas of paediatrics from the community to tertiary units; they can be more prone to respiratory infections and may have comorbidities that increase hospital attendance. Tracheostomy-related emergencies are associated with significant morbidity and potential mortality; however, the majority of tracheostomy-related complications are preventable.